Clinical, immunophenotype and cytogenetic profile of acute lymphoblastic leukemia in children at tertiary health care centre in India - Sirisha Rani Siddaiahgari; M A Awaghad; M S Latha (Wolters Kluwer Medknow Publications, 2015)
Objective: Data on acute lymphoblastic leukemia (ALL) in Indian children being limited, we analyzed the clinical, immunophenotype and cytogenetic profile of ALL in our pediatric patients. Materials and Methods: This was a prospective and retrospective observational study in which data of 103 children with ALL, aged three months to 18 years were analyzed. Results: Definite male preponderance (70.87%) was observed, 58.25% patients were aged between two to five years. Common clinical features included fever (92.33%), pallor (87.38%), hepatomegaly (85.44%) and splenomegaly (83.50). central nervous system involvement was seen in 6.80% and tumor lysis syndrome in 32.04% patients. Hemoglobin was <5 gm/dl in 43.69%, between 5-10 gm/dl in 45.63% patients; white blood cell count between 5,000-50,000/hpf seen in 69.90%, >50,000 in 20.39% patients. Platelet count was <50,000 cells/hpf in 48.54%. Blast cells in peripheral smear present in 67.96% patients of 97 in whom immunophenotyping was done, 82.44% were Pre B cell ALL. Pre T and T cell ALL was seen in 15/97 (15.46%) patients. Karyotyping revealed hyperdiploidy in 9/89, hypodiploidy in 2/89, miscellaneous changes in 35 patients. FISH analysis in 63 patients revealed Philadelphia chromosome positivity in seven (11.11%). MLL gene was positive in 12.70%. TELAML was positive in 13.64% (3/22) patients. 97.06% patients went in to remission post induction. Conclusion: Most of our patients come under standard risk by their age, WBC count, immunophenotyping and cytogentic analysis. We suggest larger multi-centric studies even in developing countries to understand the clinical profile and RT-PCR technique in cytogenic analysis for better risk stratification to help in risk adopted therapy.